Combination of Gada and GRA Methods in Decision Support System for Determining Permanent Employees - Matondang, Riski Pransiskus; Sianturi, Charles Jhony Mantho (Jurnal ICT : Information and Communication Technologies, 2025)
Determining permanent employees is an essential aspect of human resource management, as it affects the stability, productivity, and sustainability of a company. This decision-making process often faces challenges such as subjectivity in assessment and limitations in processing employee performance data. Therefore, a Decision Support System (DSS) is needed to assist management in determining permanent employees in a more objective, accurate, and structured manner. This study proposes a combination of Gada and Grey Relational Analysis (GRA) methods in the design of a web-based DSS at PT. Medan Bajaindo. The Gada method is applied to determine the weight of criteria based on their importance level, while the GRA method is used for ranking employee alternatives by calculating their closeness to the ideal solution. The system is developed on a web-based platform, making it accessible for management. The test results show that the combination of Gada and GRA methods can provide more accurate recommendations for determining permanent employees compared to manual evaluation. Thus, this system is expected to support companies in making decisions that are more objective, transparent, and efficient.